A inquietude do homem segundo Agostinho: um estudo do tema nas Confissões, Livros I, VIII e X - Andreatta, Danilo [UNESP] (2014)
Saint Augustine considers that man naturally possesses the will of happy life and truth. He recognizes himself as a restless being and that wants to find the rest. In the work Confessions, reports his error and the steps of his conversion. Investigating his own interiority, finds God in memory and simultaneously as one that transcends it. While waiting the possession of beatitude, lives the danger of concupiscences.